Fabrication of melt spun fiber coating on metal implants - Nurul Afiqah Suandi (2019)
Dental implants have been around for so many years as a solution for tooth loss. Despite the high success rates of current dental implants, the surgery still poses some risks of failures due to the procedures involved such as drilling. In addition, current dental implant procedures can take months. This project aims to create a new design of dental implants that can reduce the risks in procedure and usage of dental implants and also reduce the amount of time needed for its procedure. The dental implant of interest was intended to be fabricated via means of additive manufacturing through the selective laser melting technique which allows customisation on its shape – a replica of the original tooth of the user. After which, an addition to the implant is a fiber coating made of a copolymer - Poly (L-lactide-co-ɛ-caprolactone) (PLC) – which aims to replace the need for screw threads like in current dental implant designs. The purpose of PLC fiber coating is to facilitate and enhance the primary stability (i.e. immobility) of a dental implant. This final year project was focused on studying the fiber coating material. The fiber fabrication technique of choice was melt-spinning due to its advantages in production of fibers. PLC was chosen due to its biocompatibility and mechanical strength for fabrication as fibers. PLC was melted and spun around mandrels to form films that were used as samples for tests. Observations on the outcome of PLC fiber films showed that PLC experiences thermal degradation with the use of melt spinning technique during fabrication. The thermal degradation then affected the mechanical properties of the PLC fibers. Compressibility tests were conducted to observe the recovery behavior of PLC from subjected compressions of 15-18% of initial film thickness. PLC was found to be able to recover upon compression due to its elastic properties but with no concluded behavioural trend in recovery results – a large range of between 18 to 40% of the compression amount (measured in thickness). Hence it is recommended that this study be repeated but with modifications to the fabrication of samples. Degradation studies were also conducted to observe the rate of degradation of PLC fibers within a period of 21 days. The samples were subjected to different temperature conditions (room temperature [as a control], 37°C [to simulate body temperature] and 60°C [as an accelerated degradation study]). It was found that PLC had a slow degradation rate when incubated under 37°C, retaining at least 80% of its original weight after 21 days. Forecasts done predicted that PLC will retain at least 62.9% of its original weight after 6 weeks and will be fully degraded by approximately 4 months of indwelling. Microstructure analysis supported the idea that PLC fibers will be able to replace screw threads and the customizability of its fabrication will allow various advantages in the surface modification of the final implant. Recommended future works would be to further characterise the behavior of PLC fibers as coating on dental implants, to optimise the fabrication parameters of PLC fibers and study the bulk material used to make the implant.